خدمات الصیرفة الالكترونیة في البنوك الجزائریة دراسة حالة القرض الشعبي الجزائري - أوصغير , الويزة (Finance and Business Economies Review, 2018)
This study aims to identify the reality of the availability of electronic banking services in Algerian banks, what distinguishes the electronic banking service in the Algerian banks is that are still at an initial stage through the introduction of debit cards and the introduction of some ICT in the banking sector. The Algerian People's Loan is one of the oldest bank institutions in Algeria which has been able to develop its customer service systems by introducing the advanced system of cards to its banking services, whether by drawing or paying at the national or international level, and to using the method of providing the service across the line.